Vitamin D Status and its Association with Homocysteine, Insulin and Insulin Resistance among Type II Diabetes Mellitus in Iraqi Patients - Luay Qasim Abdulhameed (Journal of Global Pharma Technology, 2018)
The study aimed to assess vitamin D level and its impact on homocysteine, fasting blood glucose,Glycated hemoglobin, insulin and insulin resistance. The study conducted in Baqubah city, Diyala province, Iraq. Study period from September 2017 to June2018. Totally123samples, (78) samples of patients type II with mean age (54.75±1.11), and (45) samples with mean age (37.24±0.79) as control group. Vitamin D, homocysteine, fasting blood glucose (FBG), Glycated hemoglobin (HbA1C), insulin and insulin resistance (HOMO-IR) were measured. Results indicated presence of significant higher (p ≤ 0.001) in fasting blood glucose, glycated hemoglobin, insulin, insulin resistance and homocysteine among diabetic patients type II compared to control. Whereas, vitamin D was significant lower (P<0.001) in diabetic patients type II compared to control. In addition vitamin D level was inversely correlation (P<0.01) with fasting blood glucose, glycated hemoglobin. Moreover, it was inversely correlation (P<0.001) with insulin, insulin resistance and homocysteine.The study concluded thatvitamin D was inversely correlation with all variables in current study and it has important effect on these variables through several mechanisms at level gene expression in diabetic patients. Keywords: Diabetes mellitus,Vitamin D, Homocysteine,Insulin, Insulin resistance.